Optimization of Technological Processes of Waste Processing and Dynamics of Energy Capacity - Karimova, G.X. (Herald of Azerbaijan Engineering Academy, 2021)
The article considers the optimization of technological processes of utilization of waste and the dynamics of energy in mining enterprises and studies the methods of estimating the parameters of these mathematical models by the nonlinear method of the least squares. It has been established that the practical search for environmentally rational technological solutions can be reduced to solving problems of linear mathematical programming. The main results of optimization of technological processes are obtained in the form of equations of the optimal time for each technological operation.